2019
DOI: 10.1111/pbi.13234
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional landscape of pathogen‐responsive lncRNAs in rice unveils the role of ALEX1 in jasmonate pathway and disease resistance

Abstract: Summary Plant defence is multilayered and is essential for surviving in a changing environment. The discovery of long noncoding RNAs (lncRNAs) has dramatically extended our understanding of post‐transcriptional gene regulation in diverse biological processes. However, the expression profile and function of lncRNAs in disease resistance are still largely unknown, especially in monocots. Here, we performed strand‐specific RNA sequencing of rice leaves infected by Xanthomonas oryzae pv. Oryzae (Xoo) in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 50 publications
0
78
0
Order By: Relevance
“…In tomato, a plausible model for TYLCV-induced diseases and host antiviral immunity was uncovered; that is, lncRNAs interact with the IR-derived vsRNAs to control disease development during TYLCV infection, which provide an effective strategy for the control of plant viral pathogens [67]. In rice, the connection between lncRNAs and the JA pathway in the regulation of bacterial blight was confirmed, which provided a novel insight into plant disease resistance [68].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In tomato, a plausible model for TYLCV-induced diseases and host antiviral immunity was uncovered; that is, lncRNAs interact with the IR-derived vsRNAs to control disease development during TYLCV infection, which provide an effective strategy for the control of plant viral pathogens [67]. In rice, the connection between lncRNAs and the JA pathway in the regulation of bacterial blight was confirmed, which provided a novel insight into plant disease resistance [68].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, many studies reported that lncRNAs play important roles in plant defense against pathogens [66][67][68]. In tomato, a plausible model for TYLCV-induced diseases and host antiviral immunity was uncovered; that is, lncRNAs interact with the IR-derived vsRNAs to control disease development during TYLCV infection, which provide an effective strategy for the control of plant viral pathogens [67].…”
Section: Discussionmentioning
confidence: 99%
“…The basic strategy for the functional verification of plant lncRNAs is still a strategy based on acquisition/loss of function, i.e., studies on lncRNA overexpression based on genetic transformation platforms or loss-of-function studies based on clustered regularly interspaced short palindromic repeat (CRISPR)-associated protein 9 (Cas9) systems, RNAi and siRNA. Yu et al [52] obtained lncRNA ALEX1 (a full-length of 294 nt) through the rapid amplification of cDNA ends (RACE) technology, and the construction of an overexpression vector and genetic transformation revealed that ALEX1 could activate the jasmonic acid signaling pathway and affect resistance to bacterial blight in rice. Cui et al [43] analyzed the overexpression and silencing of lncRNA33732 in tomatoes and found that lncRNA33732 can enhance the resistance of tomatoes to Phytophthora infestans by inducing the expression of respiratory oxidase homolog (RBOH) and the accumulation of H 2 O 2 .…”
Section: Strategies Based On Acquisition/loss Of Functionmentioning
confidence: 99%
“…The rice lncRNAs in response to the infection of Xanthomonas oryzae pv. was identified, and the regulation of lncRNA-mediated JA pathway on rice resistance was described [32]. Some lncRNAs have recently been identified in plants but limited studies have investigated whether biocontrol bacteria induce plant resistance to diseases.…”
Section: Certain Lncrnas Participate In Sneb821-induced Tomato Resistmentioning
confidence: 99%